Kinetika reaksi polimerisasi urea-asetaldehid dalam proses enkapsulasi urea - Indah Purnamasari; Rochmadi Rochmadi; Hary Sulistyo (Jurnal Rekayasa Proses, 2012)
The function of urea encapsulation is to control its release in water, thus increasing effectiveness of using urea and reducing environmental pollution. Microcapsule shell is formed directly on the surface of urea particles called in-situ polymerization. This research aimed to study the kinetics of the polymerization reaction of urea and acetaldehyde in the urea encapsulation process.Urea and acetaldehyde in the ratio of 1:1.2 mol/mol were placed in an erlenmeyer equipped with a thermometer and cooler. The reaction was run for 2 hours in erlenmeyer and sample was taken every 20 minutes. The amount of remaining acetaldehyde was determined by sodium sulfite method and grain size was measured by optical microscope and image pro software. Variables investigated were reaction temperatures (5 - 15°C), particle sizes (14, 18, and 25 mesh), and pH (2 - 4). Reaction rate and diffusivity constants were determined through fitting the experimental data and proposed model.The results showed that the higher temperature and grain size, the higher conversion was. Lower pH (more acid) provides higher conversion but urea particle was seen slightly swelling during the reaction, and also slightly sticky. Addition reaction was much faster than condensation reaction. The proposed reaction kinetics model fitted reasonably well to the experimental data. The process was best conducted at 15°C, 14 mesh, pH 4 and 120 minutes time of reaction which result in 63.38% conversion. Polymer product of urea-acetaldehyde obtained at this condition was slightly harder than that at other conditions.